Exosomes derived from pulmonary metastatic sites enhance osteosarcoma lung metastasis by transferring the miR-194/215 cluster targeting MARCKS - Yu, Pei; Han, Yubao; Meng, Lulu; Tian, Yanyuan; Jin, Zhiwei; Luo, Jun; Han, Chao; Xu, Wenjun; Kong, Lingyi; Zhang, Chao (Acta pharmaceutica Sinica. B, 2024)
Osteosarcoma, a prevalent primary malignant bone tumor, often presents with lung metastases, severely impacting patient survival rates. Extracellular vesicles, particularly exosomes, play a pivotal role in the formation and progression of osteosarcoma-related pulmonary lesions. However, the communication between primary osteosarcoma and exosome-mediated pulmonary lesions remains obscure, with the potential impact of pulmonary metastatic foci on osteosarcoma progression largely unknown. This study unveils an innovative mechanism by which exosomes originating from osteosarcoma pulmonary metastatic sites transport the miR-194/215 cluster to the primary tumor site. This transportation enhances lung metastatic capability by downregulating myristoylated alanine-rich C-kinase substrate (MARCKS) expression. Addressing this phenomenon, in this study we employ cationic bovine serum albumin (CBSA) to form nanoparticles (CBSA-anta-194/215) electrostatic interaction with antagomir-miR-194/215. These nanoparticles are loaded into nucleic acid-depleted exosomal membrane vesicles (anta-194/215@Exo) targeting osteosarcoma lung metastatic sites. Intervention with bioengineered exosome mimetics (anta-194/215@Exo) not only impedes osteosarcoma progression but also significantly prolongs the lifespan of tumor-bearing mice. These findings suggest that pulmonary metastatic foci-derived exosomes initiate primary osteosarcoma lung metastasis by transferring the miR-194/215 cluster targeting MARCKS, making the miR-194/215 cluster a promising therapeutic target for inhibiting the progression of patients with osteosarcoma lung metastases.